Državljanske prakse mladih z vidika digitalne neenakosti in intersekcionalnosti - Hrženjak, Majda (Teorija in praksa, 2014)
The political participation of youngsters appears to be ambivalent and dependant on multiple social factors which may produce segregation effects on the activity of diverse social groups. As communicative technologies play an important role in youth citizenship practices, the author of this contribution analyses the potential of the concept of digital inequality in understanding the political in(activity) of youth. In competition with the notion of digital inequality which largely leans on technological determinism, the perspective of intersectionality is proposed which enables a socially embedded analysis of the heterogeneity of youth and their uses of communicative technologies for political purposes by taking account of individual- or group-specific social locations, their multiple belongings, positionality in power relations, intersection of different life domains as well as micro-identity, meso-organisational and macro-normative dynamics.
Keywords: Citizenship; družba; Državljanstvo; Informacijska tehnologija; Information technology; mladi; Mladi odrasli; Political participation; Politična participacija; society; Young adults